2006
DOI: 10.1038/sj.bjc.6603347
|View full text |Cite
|
Sign up to set email alerts
|

Vinflunine: a new active drug for second-line treatment of advanced breast cancer. Results of a phase II and pharmacokinetic study in patients progressing after first-line anthracycline/taxane-based chemotherapy

Abstract: To evaluate the single agent activity, pharmacokinetics and tolerability of the novel tubulin targeted agent vinflunine (VFL) (320 mg m À2 q 21 days) as second-line chemotherapy in patients with metastatic breast carcinoma (MBC). All patients had disease progression after anthracycline/taxane (A/T) therapy. They could have received a nonanthracycline adjuvant treatment and subsequently received a first-line A/T combination for advanced/metastatic disease; or relapsed 46 months after completion of adjuvant A/T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Vinflunine-related adverse events were not cumulative and included mostly grade 3-4 neutropenia, fatigue, and constipation (69,71).…”
Section: Vinca Alkaloids Vinfluninementioning
confidence: 99%
See 1 more Smart Citation
“…Vinflunine-related adverse events were not cumulative and included mostly grade 3-4 neutropenia, fatigue, and constipation (69,71).…”
Section: Vinca Alkaloids Vinfluninementioning
confidence: 99%
“…Recently completed clinical trials showed the activity of vinflunine in patients with advanced transitional cell carcinoma of the urothelium (TCCU; refs. 69,70), breast (71), NSCLC (72), and malignant pleural mesothelioma (73). In a recently reported phase 3 trial, the efficacy of vinflunine was equivalent to docetaxel in pretreated patients with NSCLC (74).…”
Section: Vinca Alkaloids Vinfluninementioning
confidence: 99%
“…The high efficacy of vinflunine in a breast tumour xenograft model [176] prompted its evaluation in phase I studies for metastatic breast cancer, wherein it produced encouraging results [200] . A recent phase II trial supported the use of vinflunine in metastatic breast cancer, particularly as a second-line treatment following anthracycline/taxane chemotherapy [196] .…”
Section: Vinca Alkaloidsmentioning
confidence: 99%
“…Vinflunine is a bifluorinated derivative of vinorelbine [196] and is the latest vinca alkaloid to reach the clinic. Although vinflunine initiates apoptosis by inhibiting mi-totic spindle formation [197] , its effects differ subtly from those of established vinca alkaloids [198,199] .…”
Section: Vinca Alkaloidsmentioning
confidence: 99%
“…Overall median progression-free survival and median survival were 3.7 and 14.3 months, respectively [8].…”
Section: Introductionmentioning
confidence: 99%